Humanities 3.0 Era and Humanities Engineering - Dr.Yongwook Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This challenging humanities research methodology, which can be conceptualized as “Humanities engineering,” declares the beginning of the 3.0 humanities era. If traditional humanities was humanities 1.0, digital humanities, which actively attempted to recruit IT as a research methodology is 2.0, and humanities engineering that aims to view humans and society from a deeper and broader viewpoint than technology by taking the help of technology is humanities 3.0. Changes in social needs and requirements also reconfigure the role of humanities education. The twenty-first century talent is a self-directed learner who can produce knowledge based on given information and acquire wisdom in the process. The core of intellectualization is creative thinking that addresses information. All newness starts from what is old and familiar. Although technology looks at the future, thinking remembers the past. Reading, understanding, and analyzing the classics is what humanities education can do best. The goal of university education in the digital period is to cultivate the talent needed in the knowledge information period to strengthen humanities education. Humanities education helps us to proceed and maintain moral value as humans; it teaches us the expansion of thinking that sparks the commercialization of information.